Making WhatsApp work: An exploration of how South Africans earn a livelihood through a free messaging application - de Villiers, Ockert (University of the Witwatersrand, Johannesburg, 2024)
The Master’s Research Project examines, through the medium of long-form journalism, how South Africans use WhatsApp to earn a livelihood. The project consists of two parts. The first is a theoretical and scholarly exploration of how messaging and chat applications bridge the digital divide and provide potential customers access to goods and services beyond the physical space. The aim is to highlight how relatively inexpensive technology can serve as a tool to earn a living. The research aims to understand better how individuals may appropriate WhatsApp to launch, scale or supplement their operations. As a free and easy-to-use application that has reached ubiquity in South Africa, WhatsApp has become a valuable tool in the hands of those who have seen its value beyond its intended design. The second part of the project weaves the research, interviews with subject-matter experts, and the stories told by the participants into a long-form journalistic essay. The narrative is interspersed with the first-person storytelling of the author’s experiences and observations throughout the explorative process.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of School of literature, language and media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; WhatsApp economy; social commerce; WhatsApp commerce; SDG-9: Industry, innovation and infrastructure